Classificazione OBIA automatica di elementi stradali acquisiti con laser scanner - Vera Costantini (mediaGEO soc. coop., 2021)
This paper shows the results obtained by classifying point clouds from LiDAR using Object Based Image Analysis (OBIA) with Trimble's eCognition software. This is a pilot project that demonstrates promising prospects for the application of OBIA analysis to the field of laser acquisitions. The point cloud acquired with LiDAR technology was automatically classified within eCognition Developer 10 software, in order to extract the main elements of a motorway axis. The result is excellent, also considering the fact that there was no manual editing. We reached an accuracy of 86% in identification of the targets.